2018
DOI: 10.1103/physrevd.97.122004
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of cosmic ray air showers with Tunka-Rex data using template fitting of radio pulses

Abstract: We present an improved method for the precise reconstruction of cosmic-ray air showers above 10 17 eV with sparse radio arrays. The method is based on the comparison of measured pulses to predictions for radio pulse shapes by CoREAS simulations. We applied our method to the data of Tunka-Rex, a 1 km 2 radio array in Siberia operating in the frequency band of 30-80 MHz. Tunka-Rex is triggered by the air-Cherenkov detector Tunka-133 and by scintillators (Tunka-Grande). The instrument collects air-shower data sin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 26 publications
1
64
0
1
Order By: Relevance
“…Detecting the radio emission of showers may bring us closer to an answer. Either through the detection of air showers, exploiting the excellent energy and composition resolution that comes with the radio method [1][2][3][4][5], or through the detection of the neutrino counterpart of ultra-high energy cosmic rays. Neutrinos can either be generated in interactions at the sources (astrophysical neutrinos), allowing for multi-messenger detection of for example gamma-rays and neutrinos [6][7][8] or as cosmogenic neutrinos [9][10][11].…”
Section: Introduction and Scientific Motivationmentioning
confidence: 99%
“…Detecting the radio emission of showers may bring us closer to an answer. Either through the detection of air showers, exploiting the excellent energy and composition resolution that comes with the radio method [1][2][3][4][5], or through the detection of the neutrino counterpart of ultra-high energy cosmic rays. Neutrinos can either be generated in interactions at the sources (astrophysical neutrinos), allowing for multi-messenger detection of for example gamma-rays and neutrinos [6][7][8] or as cosmogenic neutrinos [9][10][11].…”
Section: Introduction and Scientific Motivationmentioning
confidence: 99%
“…One of the goals of the Tunka-Rex detector was the development and test of techniques for the precise reconstruction of air-showers. This goal was successfully achieved: analytical and Monte-Carlo-driven methods were developed and semi-blindly cross-checked with Tunka-133 reconstruction [32,33,23]. Besides this, Tunka-Rex actively uses machine learning techniques [34,35] and develops methods for reconstruction of inclined events [36].…”
Section: Cosmic-ray Setupsmentioning
confidence: 99%
“…Left: Mean atmospheric depth of the shower maximum as a function of the energy reconstructed by experiments measuring the electromagnetic component of airshowers[22,23,24,25], the model curves are from Refs [26,27,28]…”
mentioning
confidence: 99%
“…To acquire sufficient data in the EeV energy domain, it is necessary to cover areas from tens to thousands of square kilometers, what implies the deployment of sparse arrays with distances between antenna stations from tens to thousands of meters. The hardware and methods for the sparse antenna arrays were developed and successfully tested in AERA and Tunka-Rex [6,[17][18][19][20][21][22], which has shown that radio arrays for air-shower detection are ready for the installation on the large areas. This success have brought a motivation to build large-scale radio arrays with areas of thousands square kilometers.…”
Section: Progress In the Detection Of Air-showers With Radiomentioning
confidence: 99%
“…• Precision for energy and shower maximum. In the last years it was proven that the resolution of radio detectors can achieve 10-15% for the energy and 20-40 g/cm 2 for the depth of shower maximum [5,6] depending on energy and on the configuration of the detector. These numbers are comparable with the precision achievable using optical methods of air-shower detection.…”
Section: Introductionmentioning
confidence: 99%